2009
DOI: 10.1074/jbc.m901429200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of Hydrophobic Residues in Both MD-2 and Toll-like Receptor 4 in Activation by Endotoxin

Abstract: Gram-negative bacterial endotoxin (i.e. lipopolysaccharide (LPS)) is one of the most potent stimulants of the innate immune system, recognized by the TLR4⅐MD-2 complex. Direct binding to MD-2 of LPS and LPS analogues that act as TLR4 agonists or antagonists is well established, but the role of MD-2 and TLR4 in receptor activation is much less clear. We have identified residues within the hairpin of MD-2 between strands five and six that, although not contacting acyl chains of tetraacylated lipid IVa (a TLR4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 42 publications
4
105
1
Order By: Relevance
“…9). Leu-125 sits on the Phe-126 loop, which is essential for receptor dimerization (13,14). However, Phe-126 does not directly bridge dimerization in the hTLR4⅐hMD-2⅐LPS co-crystal structure (12); it actually folds back toward hMD-2 to accommodate the extra acyl chain of LPS that lies on hMD-2 surface in the co-crystal structure (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9). Leu-125 sits on the Phe-126 loop, which is essential for receptor dimerization (13,14). However, Phe-126 does not directly bridge dimerization in the hTLR4⅐hMD-2⅐LPS co-crystal structure (12); it actually folds back toward hMD-2 to accommodate the extra acyl chain of LPS that lies on hMD-2 surface in the co-crystal structure (12).…”
Section: Discussionmentioning
confidence: 99%
“…2a, only the upper portion of the fourth acyl chain on lipid IV A was expected to be involved in hydrophobic interactions with mMD-2 and mTLR4 at the dimerization interface. In comparison, hydrophobic interactions between mMD-2 and mTLR4 at the dimerization interface in the mTLR4⅐mMD-2⅐lipid IV A model were expected to be similar to those in the hTLR4⅐hMD-2⅐LPS co-crystal structure (12), because virtually all hydrophobic residues on MD-2 and TLR4 essential for receptor dimerization (13,14) are conserved between the two species (12). In addition, mMD-2 has the hydrophobic Leu-125 in place of Lys-125 in hMD-2 ( Fig.…”
Section: Human and Mouse Md-2 Have Different Surface Chargesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently determined crystal structure of the TLR4⅐MD-2-RaLPS complex and a model, based on mutations of MD-2 and TLR4 demonstrated the occupation of the complete pocket of MD-2 with acyl chains of the LPS. Therefore, even a small ligand bound to its thiol group could (43,44) interfere with lipid A binding, particularly with an agonistic chemotype, that typically contains six acyl chains. Acrolein has been reported to inhibit the NF-B activation by endotoxin (45), and it has recently been shown that it suppresses the LPS-induced TLR4 dimerization upstream of MyD88 (46).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the nature of its main PAMP, lipopolysaccharide (LPS), a glycolipid from Gramnegative bacterial outer membranes [12,[47][48][49][50][51][52][53][54]. Only small amounts of LPS are required to stimulate the TLR4 pathway and hence alert the immune system to invading pathogens, and overstimulation of this pathway can lead to sepsis.…”
Section: Structure and Dynamics Of Tlr4/md-2mentioning
confidence: 99%